Ecology, Religion, and Environment: Sambori Indigenous Religion’s Perspectives towards Nature and Conservations. - Nurdin, Nurdin (The Sunan Ampel Review of Political and Social Sciences, 2022)
This paper aimed to examine cosmological aspects in Sambori indigenous community perspectives towards nature and conservations in which the inter-subjective relational relationship between human being and non-human being becomes the primary resource to protect the environment and the surrounding area in Sambori indigenous community particularly with their respective sacred land, wellspring, and forest. This study employed a qualitative approach which the primary resources are literature studies and internet observations, the data were then descriptively and qualitatively described. This study found that the inter-subjective relational relationship between the Sambori indigenous people and non-human being lies on their daily lives and rituals, particularly related to their primary source of livelihood which relies on natural resources. They believed that their surrounding area has sacred sites where the Holy Being, locally known as Parafu and the other respected ancestral spirit resides. Therefore, they strongly believe that natural resources including land, water, forest, and so forth cannot be separated from their everyday life. They have unique way to understand and to engage with their natural resource. This perspective proposes mutual, ethical, and responsible commitment between human being and the other being. Some spiritual ceremonies are performed such as Pamali Manggodo and Balaleha Music Art as a means to engage, interact and connect to the Holy beings to ask for help, safety, and peaceful life, as well as to refuse reinforcements, particularly for their agricultural activities.